Pengaruh Lingkungan Kerja Fisik, Pengawasan Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Persada Nawa Kartika Kertosono Kabupaten Nganjuk - Ahmad Akbar Husna M; Endah Kurniawati; Brahma Wahyu Kurniawan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This research explains the influence of the physical work environment, supervision and employee work discipline on the performance of PT employees. Persada Nawa Kartika Kertosono Nganjuk Regency. The analysis technique in this research uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, partial tests (t tests) and simultaneous tests (f tests). The population is 47 employees. The sampling technique used saturated samples, the number of samples in the study was 36 permanent employees. Research results (1) The level of significance of the Sig value. 0.069 > 0.05 and the value of tcount < ttable (1.881 < 2.032) means that the physical work environment does not have a partial and significant effect on employee performance. (2) Sig value. 0.295 > 0.05 and the value of tcount < ttable (1.064 < 2.032) means that supervision has no partial and significant effect on employee performance. (3) Sig. 0.017 < 0.05 and the value of tcount < ttable (2.529 > 2.032) means that work discipline has a partial and significant influence on employee performance. (4) It is concluded that Sig.F 0.000 is greater than 0.05. It was concluded that physical work environment variables, supervision and work discipline simultaneously had a positive and significant effect on performance. (5) The results of the multiple linear analysis test are as follows: Y = 4.128 + 0.202X1 + 0.211X2 + 0.451X3